2016
DOI: 10.1097/sla.0000000000001646
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role for Intravenous Iron in Perioperative Patient Blood Management in Major Abdominal Surgery

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
301
3
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(323 citation statements)
references
References 46 publications
7
301
3
12
Order By: Relevance
“…Preoperative iron deficiency is associated with higher perioperative transfusion rates . Controlled clinical trials have demonstrated that correction of iron deficiency with or without improvement in preoperative anaemia resulted in lower rates of RBCT . These controlled studies had protocols governing patient management which might include carefully defined timelines between screening for, and correction of, iron deficiency in relation to elective surgery, predefined RBCT triggers and other aspects of PBM.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Preoperative iron deficiency is associated with higher perioperative transfusion rates . Controlled clinical trials have demonstrated that correction of iron deficiency with or without improvement in preoperative anaemia resulted in lower rates of RBCT . These controlled studies had protocols governing patient management which might include carefully defined timelines between screening for, and correction of, iron deficiency in relation to elective surgery, predefined RBCT triggers and other aspects of PBM.…”
Section: Discussionsupporting
confidence: 86%
“…Our results indicate PIT negated the effect of iron deficiency on postoperative RBCT, leading to lower odds of perioperative RBCT. While this is consistent with the findings in controlled clinical trials , our study differs in that our cohort were transfused at the discretion of the treating surgeons/anaesthetists, rather than following predefined trial criteria for postoperative RBCT. Due to the nature of the study, it was not possible to determine the trigger(s) for RBCT in every case.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In the previously mentioned study by Hirasawa et al ., it was demonstrated that sarcopenic patients showed significantly lower haemoglobin levels than non‐sarcopenic patients. As recently shown in a randomized controlled trial, patients with iron‐deficiency anaemia undergoing major open abdominal surgery showed significantly reduced blood transfusions and length of hospital stay, when administered perioperative intravenous iron . Perioperative iron transfusion could therefore complement the nutritional support programme in sarcopenic patients with iron‐deficiency anaemia.…”
Section: Discussionmentioning
confidence: 78%
“…The availability of an easy‐to‐follow, diagnostic algorithm is desirable . Intravenous iron is efficacious, safe and should be used in patients in whom oral iron is not tolerated, or if surgery is planned in less than 4‐6 weeks after the diagnosis of iron deficiency . It is notable that most effective increments of Hb‐levels (∆Hb of 1·5 and 3·9 g/dl) can be reached when intravenous iron was administered between 2 and 4 weeks before surgery .…”
Section: Anaemia Management Before An Interventionmentioning
confidence: 99%